2015
DOI: 10.1088/1367-2630/17/10/105003
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and violation of classical inequalities in the Hawking radiation of flowing atom condensates

Abstract: We consider a sonic black-hole scenario where an atom condensate flows through a subsonicsupersonic interface. We discuss several criteria that reveal the existence of non-classical correlations resulting from the quantum character of the spontaneous Hawking radiation (HR). We unify previous general work as applied to HR analogs. We investigate the measurability of the various indicators and conclude that, within a class of detection schemes, only the violation of quadratic Cauchy-Schwarz inequalities can be d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 51 publications
(147 reference statements)
1
37
0
Order By: Relevance
“…By (2) theoretical prediction for this type of system would be near-maximal entanglement for all but the longest wavelengths 28 . Approximately maximal entanglement is indeed observed for the larger k-values.…”
Section: Measuring the Entanglement Of The Hawking Pairsmentioning
confidence: 98%
“…By (2) theoretical prediction for this type of system would be near-maximal entanglement for all but the longest wavelengths 28 . Approximately maximal entanglement is indeed observed for the larger k-values.…”
Section: Measuring the Entanglement Of The Hawking Pairsmentioning
confidence: 98%
“…In particular, the function Ψ SH 0 (x) is continuously connected to the homogeneous subsonic plane wave solution, and since it has the larger amplitude inside the well, it represents the true ground state of the system, as can be inferred from Equation (21). Hence, the BHL solution Ψ BHL (x) of Equation (58) should be dynamically unstable for any length X > 0 of the well.…”
Section: Asymptotic Shadow Solitonsmentioning
confidence: 99%
“…The hypothesis that the full Hawking scenario of steady thermal radiation in horizon scenarios in general might be insensitive to shortdistance details has been disproven by the discovery that finite ergoregions in fluids with supersonic dispersion at short wavelengths are dynamically unstable ('black hole lasing') [9][10][11][12]. Other theoretical studies have also shown that many dynamically linear aspects of the Hawking scenario can be investigated with BEC analogs, including quantum entanglement across the horizon due to parametric production of paired excitations [13][14][15][16]. Finally, analog Hawking radiation has actually been observed [17][18][19] in a quasi-one-dimensional Bose-Einstein condensate (BEC).…”
Section: Introductionmentioning
confidence: 99%